Parental Guidance - Fickman, Andy.; Addario, Lisa.; Syracuse, Joe.; Tomei, Marisa; Midler, Bette; Crystal, Billy; Twentieth Century Fox Home Entertainment, Inc. ([United States] : 20th Century Fox Home Entertainment, 2013)
Old-school grandparents Artie and Diane get more than they bargained for when they get stuck babysitting their type-A daughter's overprotected kids. But things go from hectic to hysterical when Artie realizes the kids are running the house with their newfangled technology. By playing by his own rules, which include sugary snacks, old-fashioned games, and tough love, Artie manages to outsmart the kids and achieve the impossible: bringing the family closer together.
Keywords: Grandparent and child -- Drama; Families -- Drama; Technology -- Drama; Abuelos -- Teatro; Familias -- Teatro; Tecnología -- Teatro; Feature films; Fiction films; Comedy films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities